Reproductive biology of Hybopsis amblops, the Bigeye Chub, in the Flint River of Alabama - Crissy L Tarver; Bruce W Stallsmith (Southeastern Fishes Council Proceedings, 2026)
The purpose of this study was to establish a reproductive schedule and examine reproductive traits that shape fecundity of the Bigeye Chub, Hybopsis amblops Leuciscidae in the Flint River system of north Alabama. Traits associated with reproduction, growth, and maturation were assessed. Specimens were collected and examined monthly from August, 2013 until July, 2014. This Bigeye Chub population primarily spawns in April and May as indicated by gonadosomatic index (GSI), ovarian condition and clutch size. Mean GSI values began to rise in February, peaking in April and May at over 13% for females and 1.6% for males. There was a steep decline in these values from May to June for both sexes. Clutch sizes ranged from 550 to 2,566 oocytes, with females of mean 62.5 mm standard length. The largest mean clutch size was found in specimens collected in March, 2014 at 1,271. Mature oocytes, Stage IV, were relatively small in comparison to other leucisids found in the Flint River with a mean diameter of approximately 1 mm. The collection of this information is important for future comparisons showing this population’s response to environmental changes, sympatric and allopatric population comparisons, and any conservation effort based on scientific data.
Keywords: ovarian maturation; oocyte maturation; Leuciscidae; river fishes